1983
DOI: 10.1152/ajpcell.1983.245.3.c178
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic acids on intracellular pH

Abstract: By use of double-barreled pH-sensitive microelectrodes, intracellular pH was measured in isolated sheep cardiac Purkinje strands. After equimolar substitution of 20 mmol/l Cl- by several organic anions at constant extracellular pH 6.8, the rate of induced intracellular acidification was measured. For many organic acids tested, a relation was found between the rate of intracellular acidification and the product of their dissociation constant (pK'a) and diisopropylether-to-water partition ratio (p'). L-Lactate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(48 citation statements)
references
References 13 publications
2
45
0
1
Order By: Relevance
“…4 shown to induce a fall in pHi (Sharp & Thomas, 1981;Roos & Boron, 1981;De Hemptinne, Marrannes & Vanheel, 1983;Szatkowski & Thomas, 1989 advantage since a low extracellular pH has been shown to impair proton extrusion across neuronal plasma membranes (Jean, Frelin, Vigne, Barbry & Lazdunski, 1985).…”
Section: Properties Of Ipspsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 shown to induce a fall in pHi (Sharp & Thomas, 1981;Roos & Boron, 1981;De Hemptinne, Marrannes & Vanheel, 1983;Szatkowski & Thomas, 1989 advantage since a low extracellular pH has been shown to impair proton extrusion across neuronal plasma membranes (Jean, Frelin, Vigne, Barbry & Lazdunski, 1985).…”
Section: Properties Of Ipspsmentioning
confidence: 99%
“…A further complication which precluded the use of ammonia in the present work is its capability to inhibit K+-Cl-co-transport (Aickin et al 1982;Thompson et al 1988 b). Lactate was chosen in the present experiments because it permeates cell membranes in its protonated form by both passive and facilitated diffusion (Spencer & Lehninger, 1976;De Hemptinne et al 1983;Mason et al 1990). Both mechanisms promote a fall in pH1 upon exposure of a cell to a lactate-containing solution.…”
Section: Ionic Basis Of Eipp-a: a Quantitative Treatmentmentioning
confidence: 99%
“…An 470 CAUSES OF ISCHAEMIC CONTRACTILE FAILURE alternative is to try to mimic the metabolic changes accompanying ischaemia in a model with continued perfusion. Exposure to CN-leads to an increase in [Pi]i, but only to a small intracellular acidosis (Allen et al 1985;Eisner et al 1987b evidence suggests that in cardiac muscle much of this transport of lactate and protons is mediated by a lactate-proton co-transporter which can be partially blocked by cinnamate derivatives (de Hemptinne, Marrannes & Vanheel, 1983;Trosper & Philipson, 1987). Figure 3 shows an experiment in which a heart was exposed to CN-in the absence and subsequently in the presence of x-cyano-4-hydroxycinnamic acid (CHC) and 40 mM).…”
Section: Metabolic Changes During Exposure To Cn-and Chcmentioning
confidence: 99%
“…The effects of a-cyano-4-hydroxycinnamate ca-Cyano-4-hydroxycinnamate (CHC) has been reported to inhibit the transport of lactate and some other anions across the cardiac sarcolemma (de Hemptinne et al 1983;Mann, Zlokovic & Yudilevich, 1985;Trosper & Philipson, 1987;Poole, Halestrap, Price & Levi, 1989), and experiments on rat hearts have shown that lactate efflux during exposure to CN-in rat hearts is inhibited by CHC (Eisner, Peckett & Ware, 1988). CHC had relatively little effect on developed pressure and pHi under control (aerobic) conditions, when the rate of lactate production by glycolysis will be minimal (see e.g.…”
Section: Metabolic Changes During Brief Periods Of Ischaemiamentioning
confidence: 99%
“…The lactic acid molecule so produced presumably can enter cells through the process of non-ionic diffusion (followed by subsequent dissociation of the acid inside the cells) (6,7), or through a carriermediated cotransport system for the lactate anion and a proton (7,8). As a result, a prompt and severe intracellular acidosis is generated (9,10) (Fig.…”
mentioning
confidence: 99%